Faktor-Faktor Penghambat Kinerja Birokrasi Publik Di Era Otonomi Daerah - Herman Sismono (PUBLICA, 2011)
Government bureaucracy is one of the main activator elements in local governance. As a local device, bureaucracy is organized to support the implementation of local government tasks. Therefore the local government bureaucracy should be designed in a proffesional manner in order to deliver the maximum performance. But, unfortunately this time, the local government bureacracy is regarded as the main source of the failure in local governance. It is not separated from the poor performance of the bureaucracy that makes many government programs can not be optimally achieved. Some of the factors inhibiting the performance of local government that reviewed in this paper are (1) Bureaucracy does not understand who it serves, (2) The emergence of friction or discord between the head of local government (as head of the top bureaucracy) with regional parliament (DPRD) as a representation of sound of people who must be served by the bureaucracy, (3) The organizational of local government bureaucracy that is very big in terms of quality, (4) The low quality of accountability and transparency in local government bureaucracy performance, (5) The high influence of political power of regional head to units of bureaucracy, (6) Low responsiveness and sensitivity of the bureaucracy towards the problems faced by local communities.